2015
DOI: 10.1111/faf.12141
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of parasites on marine survival of Atlantic salmon: a meta‐analysis

Abstract: such Norwegian studies on Salmo salar provided a dataset for the time period 1996 to 2011 on 25 118 release groups comprising 657 624 fish released and 3 989 recaptured. The overall risk ratio 26 (RR), calculated as the probability of being recaptured in the treated group divided by the 27 probability of being recaptured in the control group, was estimated to be 1.18 (95 % CI: 1.07-281.30). The effect varied strongly between groups, quantified by Higgins measure of heterogeneity 29 (I 2 = 40.1%). Over 70% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 46 publications
3
88
0
1
Order By: Relevance
“…Salmon lice are external parasites that cause substantial economic losses to the salmon industry (Costello 2009a), and farmassisted parasitic outbreaks can reduce return rates of spawning salmon in sensitive rivers (Vollset et al 2014(Vollset et al , 2015, posing a potential threat to wild salmonid populations (Costello 2009b;Krkošek et al 2011Krkošek et al , 2013. The salmon louse has a direct life cycle that involves three planktonic larval stages that hatch from a pair of egg strings produced by an adult female: two noninfective naupliar stages and an infective copepodid stage (Hamre et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Salmon lice are external parasites that cause substantial economic losses to the salmon industry (Costello 2009a), and farmassisted parasitic outbreaks can reduce return rates of spawning salmon in sensitive rivers (Vollset et al 2014(Vollset et al , 2015, posing a potential threat to wild salmonid populations (Costello 2009b;Krkošek et al 2011Krkošek et al , 2013. The salmon louse has a direct life cycle that involves three planktonic larval stages that hatch from a pair of egg strings produced by an adult female: two noninfective naupliar stages and an infective copepodid stage (Hamre et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wild salmon returns were strongly reduced (> 50%) following years when there had been high lice levels on the salmon farm during the smolt out-migration. This result accounts for the effect of unexplained amongyear variation in returns, which probably reflects how marine survival varies naturally independent of lice-induced mortality (Vollset et al 2016). 'Correcting' for the estimated lice effect predicted that Erriff salmon returns might now be twice as large without observed anthropogenic sea lice impacts, but would probably show a similar long-term decline.…”
Section: Discussionmentioning
confidence: 90%
“…A longer-term reduction in survival may be associated with impacts that impair on-going fitness during migration. The impact of sea lice seems to vary with baseline survival of salmon; a meta-analysis of studies using anti-parasite treatments on salmon smolts found that in groups with low recapture in the control group (low baseline survival), the effect of treatment was high, while in groups with high recapture in the control group (high baseline survival), there was no effect of treatment (Vollset et al 2016). This result implies that the detrimental effect of lice is exacerbated in situations when the salmon smolts also have to cope with increased pressure from other causes of mortality, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of salinities below 20.0 psu may reduce infestation risk by salmon lice [22,23], and the probability of infestation is generally shown to decrease with increasing freshwater influence [35]. Salmon louse is a marine parasite, which can severely reduce Atlantic salmon populations in farm-intensive areas [36,37]. Whether the fish actively preferred lower salinity waters or unintentionally experienced low salinity because they were swimming close to the surface for other reasons (for instance, avoiding predation) is not known, but nevertheless, this behaviour might reduce the salmon lice infestation risk.…”
Section: Discussionmentioning
confidence: 99%